Leadership Challenges In The Vuca (Volatility, Uncertainly, Complexity, Ambiguity) Environment - Rima Pertiwi; Mochammad Ferdion Firdaus; Aris Sarjito (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractTechnological advances on various fronts led to a resource-hungry civilization. The need for considerable resources has an impact on the environmental or ecological crisis. This research uses a descriptive qualitative research method where researchers try to describe existing problems from the results of observations. VUCA is not a new concept in the face of change and the ability to adapt in a wide variety of conditions. This concept comes alive and becomes an abbreviation that every leader of the organization must instill when they want to survive and thrive.Keyword: Challenges, VUCAÂ AbstrakKemajuan teknologi di berbagai bidang menyebabkan peradaban yang haus sumber daya. Kebutuhan akan sumber daya yang cukup besar berdampak pada krisis lingkungan atau ekologis. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dimana peneliti mencoba mendeskripsikan permasalahan yang ada dari hasil pengamatan. VUCA bukanlah konsep baru dalam menghadapi perubahan dan kemampuan untuk beradaptasi dalam berbagai kondisi. Konsep ini menjadi hidup dan menjadi singkatan yang harus ditanamkan oleh setiap pemimpin organisasi ketika mereka ingin bertahan dan berkembang.Kata Kunci: Tantangan, VUCA